Identification and characterisation of a novel immune-type receptor (NITR) gene cluster in the European sea bass, Dicentrarchus labrax, reveals recurrent gene expansion and diversification by positive selection - Ferraresso, Serena (Springer-Verlag, 2009)
In the last decade, a new gene family encoding non-rearranging receptors, called novel immune-type receptors (NITRs), has been discovered in teleost fish. NITRs belong to the immunoglobulin superfamily and represent an extraordinarily divergent and rapidly evolving gene complex. Genomic analysis of a region spanning 270 kb led to the discovery of a NITR gene cluster in the European sea bass (Dicentrarchus labrax). In total, 27 NITR genes and three putative pseudogenes, organised in a tandemly arrayed cluster, were identified. Sea bass NITR genes maintain the three major genomic organisations that appear to be essentially conserved among fish species along with new features presumably involving processes of intron loss, exon deletion and acquisition of new exons. Comparative and evolutionary analyses suggest that these receptors have evolved following a “birth-and-death” model of gene evolution in which duplication events together with lineage-specific gain and loss of individual members contributed to the rapid diversification of individual gene families. In this study, we demonstrate that species-specific gene expansions provide the raw material for diversifying, positive Darwinian selection favouring the evolution of a highly diverse array of molecules. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00251-009-0398-3) contains supplementary material, which is available to authorized users.